The Impact of Stratrgic Planning and Strategic Thinking on Crisis Management: An Analytical Study on Governmental and Non-governmental Organizations in the KRI - Saeed, Sarkar Ahmed; Azam, Kosar Othman; Faraj, Shahen Mohammed; Mustafa, Nian Abubakir; Osman, Lanya Namiq (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2025)
Crises of organizational misdeeds arise when management takes certain decisions knowing the harmful consequences of the same towards the stakeholders and external parties. The purpose of this study is to determine the impact of strategic planning and strategic thinking on crisis management. The importance of our research is that crisis management, A timely and accurate response to any critical incident is critical to mitigating impacts, a successful crisis management plan can prevent delays, and strategic thinking helps you identify opportunities for change, and take advantage of them. It also helps staff anticipate crises that may occur in the future. The study was conducted through Google Form. A survey of Kurdistan Regional Government residents aged 20 to over 60 years and residents of Halabja, Suleimani and surrounding areas, through a simple Random sample. Approximately 120 respondents were recruited who were recruited through an adaptive questionnaire. After analyzing the data through SPSS and its Correlation and regression models. Finally, strategic thinking and strategic planning play a crucial role in effective crisis management. By anticipating potential crises, developing proactive strategies and implementing structured plans, organizations can better navigate uncertain and challenging situations. Overall, integrating strategic thinking and planning into crisis management processes can enhance an organization’s ability to mitigate risks, respond quickly, and recover quickly from crises.